The Improved Catheterization Is Associated With the Deeper Radial Arteries in Ultrasound-Guided Dynamic Needle Tip Positioning Technique - Tian, Yuan; Bai, Bing; Zhang, Yuelun; Che, Lu; Wang, Jin; Wang, Yi; Yu, Chunhua; Huang, Yuguang (Frontiers in Medicine, 2022)
Objective This study aimed to determine the associations between the first-attempt success and arterial depth in ultrasound-guided radial artery catheterization (RAC) with dynamic needle tip positioning (DNTP) technique. This study also aimed to further explore the cut-off depth correlated to improved first-attempt success catheterization in less time. Methods The cases undertaken by RAC within the DNTP technique between March 2019 and July 2020 were extracted from our institutional cohort database. Relevant variables were collected, including patients' demographics and catheterized information. Univariable and multivariable logistic regression analyses were performed to determine the association. The receiver operating characteristic (ROC) curve and the Youden index were used to explore the cut-off values of the arterial depth. Categorized cases according to the cut-off values, the Kaplan-Meier analysis, and the log-rank test were used to determine the difference of first-attempt success with limited catheterized time between groups. Results In this study, 119 patients were enrolled and 98 achieved first-attempt success. The first-attempt success catheterization was observed to be correlated to arterial depth (p < 0.01, odds ratio 6.47). An optimal cut-off depth of 2.25 mm was found using the Youden index (0.53) by ROC curve (area under curve 0.77). Arterial depth of more than 2.25 mm was correlated to improved first-attempt success catheterization in less time (log-rank p < 0.01). Conclusion To achieve first-attempt success catheterization using the DNTP technique, an arterial depth of more than 2.25 mm was associated with less catheterized time.